Criminal Protection of the Family in the Iraqi Legislation - Almusawi, Bassim Jameel (Faculty of Law, Hasanuddin University, 2021)
The protection of the family isÂ the basic principle for building a strong society and family protection policy is one of the most significant among the responsibilities of legislations. The current paper reviews the protection of family according to Iraqi legislation and discusses various types of crimes involving children or families according to Iraqi law. In this article doctrinal legal research was adopted and it assessed sources from both primary and secondary data. The research concludes that Iraqi legislation provides correct protection through a number of legal texts organizing the crimes against family. However, it has failed to achieve full criminal protection for the family. There are both theoretical weakness of law and the routine abuse against family in daily practice. The present paper aims to fill a critical gap in our understanding regarding deficient area in Iraqi law while dealing with the rights of members of family and proposes furtherÂ work to be done so that Iraqi legislator can provide full criminal protection for family.